Decentralization effects in ecological fiscal transfers: The case of Portugal - Nils Droste; Claudia Becker; Irene Ring; Rui Santos (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
Portugal has a unitary system in which the central government transfers funds to lower government levels for their public functions. In 2007, Portugal introduced Ecological Fiscal Transfers (EFT), where municipalities receive transfers for hosting Protected Areas (PA). We study whether introducing EFT in Portugal incentivized municipalities to designate PA and has led to a decentralization of conservation decisions. We employ a Bayesian structural time series approach to estimate the effect of introducing EFT in comparison to a simulated counterfactual time series. Quantitative results show a significant increase in the ratio of municipal and national PA designations following Portugal's EFT introduction. The analysis furthermore places emphasis on the importance of relevant municipal conservation competencies and the role of local decision makers' motivations for PA designations. Results have important implications for conservation policy-making in terms of allocating budgets and competencies in multi-level governments.
Keywords: C32; H41; H72; Q57; 330; Bayesian structural time series; ecological fiscal transfers; fiscal federalism; municipal competencies; nature conservation; Portugal